New insights in pediatrics in 2021: choices in allergy and immunology, critical care, endocrinology, gastroenterology, genetics, haematology, infectious diseases, neonatology, neurology, nutrition, palliative care, respiratory tract illnesses and telemedicine - Carlo Caffarelli; Francesca Santamaria; Ettore Piro; Simona Basilicata; Valeria Delle Cave; Marilena Cipullo; Sergio Bernasconi; Giovanni Corsello (BMC, 2022)
Abstract In this review, we report the developments across pediatric subspecialties that have been published in the Italian Journal of Pediatrics in 2021. We highlight advances in allergy and immunology, critical care, endocrinology, gastroenterology, genetics, hematology, infectious diseases, neonatology, neurology, nutrition, palliative care, respiratory tract illnesses and telemedicine.